2013
DOI: 10.4236/jbise.2013.612142
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the effects of occupational noise exposure on hypertension or cardiovascular among workers from automobile manufacturing company of Chongqing, China

Abstract: For the past few years, noise pollution has been more and more serious, and it may lead to several diseases. While the humans expose to noise in quantity for a long time, their blood pressure will change, and even cause changes in cardiac function. In our study, we attempt to find the relationship between occupational noise and hypertension and impaired hearing, cardiac function. It may be helpful to obtain some useful information on occupational noise exposure of humans. The participants were divided into noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The results of this study are in line with the research Wang et al 35 which states that blood pressure was significantly increased with working years growing in noisy group. Only in noisy group, ECG among workers worked 10-year were significantly higher than those who worked 0-year and workers who worked more than 15 years increased, which indicating that prolonged exposure to noise is a risk factor for high blood pressure.…”
supporting
confidence: 92%
“…The results of this study are in line with the research Wang et al 35 which states that blood pressure was significantly increased with working years growing in noisy group. Only in noisy group, ECG among workers worked 10-year were significantly higher than those who worked 0-year and workers who worked more than 15 years increased, which indicating that prolonged exposure to noise is a risk factor for high blood pressure.…”
supporting
confidence: 92%
“…Tao et al reported a hearing loss prevalence of 38.9% among 517 workers, who were exposed to 80.1‐118.4 dB(A) noise levels, in an automobile manufacturing company in China. Wang et al found that in a sample of 728 workers from automobile manufacturing factories, 11.4% experienced high‐frequency hearing loss with more than 50 dB threshold shift at 3‐6 kHz frequencies. In Malaysia, Tahir et al found that the incidence of NIHL in the manufacturing population was 139 per 100 000; among them, those workers in the factories manufacturing motor vehicle parts had a relatively high incidence of NIHL (eg 32%).…”
Section: Introductionmentioning
confidence: 99%
“…Stress due to general high noise pollution and occupational noise can lead to increase BP, irritation, and sleep disturbance [18]. Similarly, a study from China reported the positive association between occupational noise and hypertension while studying on workers from automobile company [19]. Sympatheticotonia-induced endothelial lesion might be the possible mechanism for hypertension caused by noise [20].…”
Section: Discussionmentioning
confidence: 99%